W.F. Massey New Zealand - Watson, James (London : Haus Pub., 2010)
The story of New Zealand both during the war and at the negotiations in Paris.
Introduction; Part 1; New Zealand to 1914; Massey's Life to 1914; New Zealand's Great War; Part 2; New Zealand's Interests; Negotiations; Reactions to the Peace Treaties; Part 3; New Zealand and the World, 1919-25; Domestic Politics, 1919-25; Legacy; Notes; Chronology; Bibliographical Note; Bibliography; Picture Sources; Index
Description based upon print version of record.
English
Includes bibliographical references and index.
Description based on publisher supplied metadata and other sources.
Keywords: Prime ministers -- New Zealand -- Biography; New Zealand -- Politics and government; New Zealand -- Foreign relations; Massey, W. F. -- 1856-1925.